Evaporative index for scheduling irrigation in plantation crops (MAUSAM, 1985)
Water balance analysis of the humid tropical Kerala, India shows that evaporative demand exceeds rainfall for five to seven consecutive months in a year. For scheduling of irrigation at 20, 30, 40, 50, 60 and 70 per cent of the available water capacity (A WC) in laterites, 1he cumulative evaporation values for coconut (Cocos nucifera Linn.), arecanut (Areca catechu}, cinnamon (Cinna-momum Zeylanica) and banana (Musa paradisiaca) have been worked out. The soil moisture in one metre depth has reached 70 per cent of the A WC within two days and 20 per cent of the AWC within 5, days for the crops studied. The cumulative evaporation values for these crops were 3 to  5 mm at 70 per cent of the AWC and 10 to 15 mm at 20 per cent of the AWC.